Excellent mechanical, tribological and anti-corrosive performance of novel Ti-DLC nanocomposite thin films prepared via magnetron sputtering method. (October 2019) - Zhang, Shidong; Yan, Mufu; Yang, Yang; Zhang, Yanxiang; Yan, Fuyao; Li, Hongtao
Abstract: Ti-doped diamond-like carbon nanocomposite thin films with different Ti contents are prepared by closed field unbalanced magnetron sputtering. Designed Ti target current increases from 0.3A to 1.0A. The effect of Ti content on microstructures and properties is investigated. The phases of nano-TiC and amorphous carbon are confirmed. The film (containing less than 50% sp 3 C content) deposited with a Ti target current of 0.4A obtains the highest hardness of 44.6 GPa, which is rarely reported. Besides, the film with a Ti target current of 0.3A exhibits the lowest the friction coefficient of 0.02 and 99.10% reduction in wear rate compared with the untreated specimen due to its lubricating effect and the gradient multilayer structure. Moreover, the films have a high open-circuit corrosion potential, a low anodic current density and a wide passivation range, indicating its enhanced corrosion resistance. Most importantly, these inspiring results demonstrated that the excellent mechanical, tribological and anti-corrosion properties can be realized simultaneously by introducing the as-deposited films with the merits of high hardness, self-lubricating and chemical inertness. Graphical abstract: Image 1